2020
DOI: 10.1097/inf.0000000000002967
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Imaging Findings in Critically Ill Children With Multisystem Inflammatory Syndrome Associated With COVID-19

Abstract: We report findings on abdominal imaging in critically ill children admitted with MIS-C. On sonography, hepatomegaly, nephromegaly, gallbladder wall edema, ascites, intestinal inflammation and mesenteric lymphadenopathy were seen, while CT showed fluid-filled small bowel loops, mural thickening of the terminal ileum, diffuse lymphadenopathy, and moderate ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 9 publications
2
28
0
1
Order By: Relevance
“…Other findings on chest radiography in this population included pleural effusions (44–82%), pulmonary consolidations (6–73%), and radiographic findings of acute respiratory distress syndrome (13%) [ 50 , 51 ]. If obtained, abdominal imaging may demonstrate small volume ascites, bowel wall thickening, gallbladder wall thickening, or abdominal lymphadenopathy [ 52 , 53 ]. Echocardiograms are performed in the majority of patients with MIS-C due to both concern for coronary artery aneurysmal dilation as well as cardiac dysfunction due to myocarditis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other findings on chest radiography in this population included pleural effusions (44–82%), pulmonary consolidations (6–73%), and radiographic findings of acute respiratory distress syndrome (13%) [ 50 , 51 ]. If obtained, abdominal imaging may demonstrate small volume ascites, bowel wall thickening, gallbladder wall thickening, or abdominal lymphadenopathy [ 52 , 53 ]. Echocardiograms are performed in the majority of patients with MIS-C due to both concern for coronary artery aneurysmal dilation as well as cardiac dysfunction due to myocarditis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common abdominal imaging features were intestinal imaging findings (24%), including colorectal (5%) and small bowel thickening (12%), intestinal distension (18%), pneumatosis (1%), and intestinal perforation (1%)[ 79 ]. Morparia et al [ 80 ] reported abdominal imaging findings in critically ill children admitted with multisystem inflammatory syndrome associated with COVID-19. Hepatomegaly, nephromegaly, gallbladder wall edema, ascites, intestinal inflammation, and mesenteric lymphadenopathy were seen on sonography, while CT showed fluid-filled small bowel loops, mural thickening of the terminal ileum, diffuse lymphadenopathy, and moderate ascites.…”
Section: Abdominal Imaging Findings In Covid-19 Patientsmentioning
confidence: 99%
“…Bowel wall thickening, lymphadenopathy, and mesenteric changes can occur anywhere in the abdomen but are most commonly located in the right lower quadrant (130) (Figure 32). A minority of patients has also demonstrated hepatosplenomegaly, splenic infarction, and increased renal echogenicity (114,116,131). Acute hepatitis, defined as elevated alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, was found in 43% of subjects in a single-center report, and may account for some of the abdominal ultrasound findings in MIS-C such as hepatomegaly, gallbladder wall thickening, and ascites (132).…”
Section: Abdominal Manifestations Of Mis-cmentioning
confidence: 99%